Towards a new model of OPAC. From information to knowledge. - Antonella Iacono (JLIS.it, 2013)
The paper analyzes the evolution of libraries electronic catalogs evidencing the new technologies of the Semantic Web and Linked Data. The essay is divided into two distinct parts. In the first part starting from critical analysis of the new generation of OPAC functional model and discovery tools proposes the need for a revision of current development paradigm that accepting the theories of information behaviour can be based on the user, on its information needs, its behaviours, and on the analysis of components that takes part of search information process. In the second part of next publication will explore the possibility that Linked Data may be the most appropriate technology to build up new OPAC based on output of knowledge within the information process.